Impact of 3D Printing on Short-Term Outcomes of Biventricular Conversion From Single Ventricular Palliation for the Complex Congenital Heart Defects - Shi, Bozhong; Pan, Yanjun; Luo, Weiru; Luo, Kai; Sun, Qi; Liu, Jinlong; Zhu, Zhongqun; Wang, Hao; He, Xiaomin; Zheng, Jinghao (Frontiers in Cardiovascular Medicine, 2021)
Background: Although Fontan palliation seems to be inevitable for many patients with complex congenital heart defects (CHD), candidates with appropriate conditions could be selected for biventricular conversion. We aimed to summarize our single-center experience in patient selection, surgical strategies and early outcomes in biventricular conversion for the complex CHD. Methods: From April 2017 to June 2021, we reviewed 23 cases with complex CHD who underwent biventricular conversion. Patients were divided into two groups according to the development of the ventricles: balanced ventricular group (15 cases) and imbalanced ventricular group (8 cases). Early and short-term outcomes during the 30.2 months (range, 4.2-49.8 months) follow-up period were compared. Results: The overall mortality rate was 4.3% with one death case. In balanced ventricular group, 6 cases received 3D printing for preoperational evaluation. One case died because of heart failure in early postoperative period. One case received reoperation due to the obstruction of the superior vena cava. In imbalanced ventricular group, the mean left ventricular end-diastolic volume was (33.6 ± 2.1) ml/m2, the mean left ventricular end-diastolic pressure was 9.1 ± 1.9 mmHg and 4 cases received 3D printing. No death occurred while one case implanted a pacemaker due to degree III atrioventricular block. Preoperationl evaluation and surgery simulation with 3D printing model helped to reduce bypass time in balanced group (p<0.05), and reduced both bypass and aorta clamp time in imbalanced group (p<0.05). All patients presented great cardiac function in follow-up period. Conclusion: Comprehensive evaluation, especially 3D printing technique, was conducive to finding the appropriate cases for biventricular conversion and significantly reduced surgery time. Biventricular conversion in selected patients leaded to promising clinical outcomes, albeit unverified the long-term results.